1962
DOI: 10.5935/0305-7518.19620013
|View full text |Cite
|
Sign up to set email alerts
|

Maculo-Anaesthetic Leprosy - Its Diagnosis and Classification

Abstract: • The present paper refers only to the "simple" nat benign lesions of leprosy and comments on the subject have theref ore been limited mainly to cover this type of lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is difficult to distinguish from Indeterminate leprosy, and some authori ties will call a lesion maculo-anaesthetic whereas others will call it indeterminate , and yet others a tuberculoid macule. Dharmendra (1962), Indian leprologists and others tend to broaden this category to include larger macules with asso ciated neural involvement, which are better considered as part of the Dimorphous type . It would appear preferable to include in maculo anaesthetic only benign patients in which there is never nerve involvement leading to disability.…”
Section: The Spectrum Of Lepro Symentioning
confidence: 99%
“…It is difficult to distinguish from Indeterminate leprosy, and some authori ties will call a lesion maculo-anaesthetic whereas others will call it indeterminate , and yet others a tuberculoid macule. Dharmendra (1962), Indian leprologists and others tend to broaden this category to include larger macules with asso ciated neural involvement, which are better considered as part of the Dimorphous type . It would appear preferable to include in maculo anaesthetic only benign patients in which there is never nerve involvement leading to disability.…”
Section: The Spectrum Of Lepro Symentioning
confidence: 99%
“…UJ vaccine was the conversion of > 76% of LL patients, 7 1 '/o of BL and 100% of BB patients to a status of lepromin positivity [25]. Retrospective studies of Dharmendara and Chatterjee [30] have shown that lepromin negative contacts of leprosy patients have much higher incidence of leprosy than those who are exposed to infection others. Immunotherapy hastens also the killing of M. leprae [28].…”
Section: Lepromin Conversionmentioning
confidence: 98%
“…Macular and hypopigmented leprosy lesions are known to occur anywhere on the body, but are often found on visible sites such as the face and lateral or dorsal aspects of extremities. 23 In a cross sectional study from central India, of the 160 leprosy patients examined, 64 (40%) presented with hypopigmented facial cutaneous lesions. 24 Facial patches of leprosy can be both pale, flat, and macular type or red raised patches in reaction.…”
Section: Pe R Si Sten T Fac Ia L Pat C He S In Leprosymentioning
confidence: 99%